Rare Mental Health Disorders Affecting Urologic Care: A Comprehensive Review - Abrahim N. Razzak; Nicholas A. Orlando; Alexis Angelette; Vinay Kumar; Danyon J. Anderson; Jamal Hasoon; Omar Viswanath; Alan D. Kaye; Joseph S. Fitz-Gerald; Nazih Khater; Ivan Urits (Health Psychology Research)
Management of mental health illnesses and needs are important in fostering psychosocial support, interprofessional coordination, and greater adherence to treatment protocols in the field of urology. This can be especially true for mental health conditions that may greatly impact the presentation of a patient in the healthcare setting with urologic symptoms. This review describes the history, epidemiology, pathophysiology, clinical presentation, and treatment of somatic symptom disorder, illness anxiety disorder, compulsive sexual behavior/hypersexuality, factitious disorder, malingering symptoms, and conversion disorder in the realm of urology. Given the newly updated psychiatric diagnoses in the *Diagnostic and Statistical Manual of Mental Disorders*, fifth edition, there has been a lack of studies reviewing how these illnesses may present in a urology patient encounter. Additionally, as these mental health illnesses may carry a rare incidence compared to other well-known mental health illness such as generalized depression or generalized anxiety disorder, we have found that the lack of provisions and recognition of the diseases can prolong the timeline for diagnosis and lead to an increased cost in both healthcare and quality of life of patients with these mental health illnesses. This review provides awareness on these mental health conditions which may greatly impact patient history and presentation within the field of urology. Additionally, urologic care providers may have an improved understanding of interdisciplinary management of such illnesses and the common symptoms patients may present with such diseases.